The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1516-89132009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Phenetic analysis of Panstrongylus megistus Burmeister, 1835 (Hemiptera: Reduviidae: Triatominae) in the State of Paraná-Brazil

Abstract: Panstrongylus megistus is an important Chagas Disease vector and is said to be one of the species that might replace

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this sense, despite the importance of knowing the genetic structure and dynamics of triatomine infestation/reinfestation for the design of chemical control activities, there are few studies in the literature. Studies with Brazilian populations of P. megistus using isoenzymes ( Kopp et al 2009 ), Random Amplified Polymorphic DNA (RAPD) ( Barbosa et al 2003 , 2006 ) and ribosomal intergenic sequences (ITS1 and ITS2) ( Cavassin et al 2014 ) revealed populations with strong population structure and reduced genetic diversity that was directly related to the geographic distance between the studied areas. This same pattern was observed in Brazilian populations of T. brasiliensis using isoenzymes ( Costa et al 1997 ), RAPD ( Borges et al 2000a , b ) and the cyt b gene ( Monteiro et al 2004 , Almeida et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, despite the importance of knowing the genetic structure and dynamics of triatomine infestation/reinfestation for the design of chemical control activities, there are few studies in the literature. Studies with Brazilian populations of P. megistus using isoenzymes ( Kopp et al 2009 ), Random Amplified Polymorphic DNA (RAPD) ( Barbosa et al 2003 , 2006 ) and ribosomal intergenic sequences (ITS1 and ITS2) ( Cavassin et al 2014 ) revealed populations with strong population structure and reduced genetic diversity that was directly related to the geographic distance between the studied areas. This same pattern was observed in Brazilian populations of T. brasiliensis using isoenzymes ( Costa et al 1997 ), RAPD ( Borges et al 2000a , b ) and the cyt b gene ( Monteiro et al 2004 , Almeida et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to investigate aspects regarding the planning and execution of vector control initiatives including the assessment of levels of genetic variation, population structure and gene flow among insect populations ( Costa et al 1997 , Noireau et al 1999 , Borges et al 2000a , b , Marcilla et al 2002 , Barbosa et al 2003 , 2006 , Almeida et al. 2008 , Kopp et al 2009 , Cavassin et al 2014 , González-Brítez et al 2014 , Panzera et al 2015 ).…”
mentioning
confidence: 99%
“…The degree of synanthropy exhibited by P. megistus varies among regions: in Argentina, Bolivia, Paraguay, and Uruguay (Lent and Wygodzinsky ) it is exclusively non‐synanthropic; from the State of Rio Grande do Sul (in the south of Brazil) to the midwest of the state of São Paulo it is hemi‐synanthropic; and in the state of Bahia and the midwest of the state of Minas Gerais it is eusynanthropic (Barbosa et al ). Some authors relate this variation to physiological and ethological differences in P. megistus populations (Dórea et al , Barbosa et al , , , Kopp et al ).…”
Section: Panstrongylus Megistus Populations Colony Code Estimated Nmentioning
confidence: 99%
“…This distribution reflects the human migrations from rural areas of Brazil to more economically developed urban centers that occurred mainly in the second half of the 20 th century, when the state of São Paulo was the primary destination for millions of Brazilians, especially those from the northeast of the country (Brito and Carvalho ). The hypothesis of passive dispersal of P. megistus is reinforced by a study based on isoenzyme analysis which showed relationships between populations in Paraná (in the south of Brazil) and in the northeast and southeast of the country (Kopp et al ).…”
Section: Panstrongylus Megistus Populations Colony Code Estimated Nmentioning
confidence: 99%